Cálculo del discriminante
1
De la ecuación: 8x² - 6x + 0 = 0, Calcula b² - 4ac
2
De la ecuación: -20x² + 19x - 3 = 0, Calcula b² - 4ac
3
De la ecuación: 8x² + 18x + 4 = 0, Calcula b² - 4ac
4
De la ecuación: -20x² + x + 1 = 0, Calcula b² - 4ac
5
De la ecuación: 2x² + 2x - 4 = 0, Calcula b² - 4ac
6
De la ecuación: -2x² - 7x - 3 = 0, Calcula b² - 4ac
7
De la ecuación: -16x² - 4x + 20 = 0, Calcula b² - 4ac
8
De la ecuación: -15x² + 4x + 3 = 0, Calcula b² - 4ac
9
De la ecuación: 9x² - 18x + 5 = 0, Calcula b² - 4ac
10
De la ecuación: -25x² - 35x - 12 = 0, Calcula b² - 4ac
11
De la ecuación: 5x² - 4x - 1 = 0, Calcula b² - 4ac
12
De la ecuación: -10x² - 8x + 2 = 0, Calcula b² - 4ac
13
De la ecuación: 3x² + x - 10 = 0, Calcula b² - 4ac
14
De la ecuación: 6x² - 16x + 10 = 0, Calcula b² - 4ac
15
De la ecuación: 6x² - 4x - 16 = 0, Calcula b² - 4ac
16
De la ecuación: 2x² + 3x + 1 = 0, Calcula b² - 4ac
17
De la ecuación: -10x² - x + 3 = 0, Calcula b² - 4ac
18
De la ecuación: -10x² + 15x + 25 = 0, Calcula b² - 4ac
19
De la ecuación: 4x² - 3x - 1 = 0, Calcula b² - 4ac
20
De la ecuación: -15x² + 20x - 5 = 0, Calcula b² - 4ac
21
De la ecuación: 5x² + 22x + 8 = 0, Calcula b² - 4ac
22
De la ecuación: 4x² - 18x + 20 = 0, Calcula b² - 4ac
23
De la ecuación: 0x² - 6x + 6 = 0, Calcula b² - 4ac
24
De la ecuación: -16x² + 20x + 0 = 0, Calcula b² - 4ac
25
De la ecuación: 15x² + 2x - 8 = 0, Calcula b² - 4ac
26
De la ecuación: 12x² - 5x - 3 = 0, Calcula b² - 4ac
27
De la ecuación: 5x² - 26x + 5 = 0, Calcula b² - 4ac
28
De la ecuación: 5x² - 30x + 25 = 0, Calcula b² - 4ac
29
De la ecuación: -16x² + 12x + 4 = 0, Calcula b² - 4ac
30
De la ecuación: -5x² + 6x - 1 = 0, Calcula b² - 4ac
31
De la ecuación: -3x² - 11x + 4 = 0, Calcula b² - 4ac
32
De la ecuación: 20x² - 2x - 4 = 0, Calcula b² - 4ac
33
De la ecuación: 9x² + 12x + 7 = 0, Calcula b² - 4ac
34
De la ecuación: 17x² - 16x + 11 = 0, Calcula b² - 4ac
35
De la ecuación: 19x² - x - 13 = 0, Calcula b² - 4ac
36
De la ecuación: 12x² - 2x - 19 = 0, Calcula b² - 4ac
37
De la ecuación: 18x² - 14x - 6 = 0, Calcula b² - 4ac
38
De la ecuación: 19x² - 3x + 21 = 0, Calcula b² - 4ac
39
De la ecuación: 14x² + 6x + 12 = 0, Calcula b² - 4ac
40
De la ecuación: - 16x² - 6x + 18 = 0, Calcula b² - 4ac
41
De la ecuación: 5x² + 11x + 3 = 0, Calcula b² - 4ac
42
De la ecuación: - 2x² - 19x + 19 = 0, Calcula b² - 4ac
43
De la ecuación: 6x² - 18x - 12 = 0, Calcula b² - 4ac
44
De la ecuación: 10x² - 7x - 18 = 0, Calcula b² - 4ac
45
De la ecuación: 6x² - 13x - 12 = 0, Calcula b² - 4ac
46
De la ecuación: - 8x² - 12x + 16 = 0, Calcula b² - 4ac
47
De la ecuación: 4x² + 15x + 19 = 0, Calcula b² - 4ac
48
De la ecuación: - 16x² + 21x + 15 = 0, Calcula b² - 4ac
49
De la ecuación: 8x² + 21x - 13 = 0, Calcula b² - 4ac
50
De la ecuación: 20x² - 17x + 12 = 0, Calcula b² - 4ac
51
De la ecuación: - 15x² + 18x - 2 = 0, Calcula b² - 4ac
52
De la ecuación: 6x² - 4x - 12 = 0, Calcula b² - 4ac
|